The CICES Journal Governance Performance Improvement on Quality Of Current Issues (Case Study of STMIK RAHARJA) - Sudaryono, Sudaryono; Rahardja, Untung; Apriani, Desy (Pandawan, 2019)
Journal Publications in STMIK Raharja is a facility for students and lecturers in conducting research, the CICES Journal is one of the journals in STMIK Raharja, which was published 1 year 2 times in February and August, the problem that occurs is the absence of an online journal google scholar indexed, and there was no information summary to make a decision and the difficulty of the prospective writer getting information about the CICES journal. To overcome this problem, a research was carried out which developed a system for improving the governance of CICES journals on published quality and quality by using SWOT analysis and the Statistical Product and Service Solutions (SPSS) method which were felt to be able to assist in data management. then transformed in the form of iMe in STMIK Raharja, is expected to overcome the existing constraints, by providing information that supports the decision-making system in Journal Publications. This system was created in collaboration with Rinfo, Rinfo Sheet, Rinfo Form and iLearning Media which are part of the 10 IT STMIK Raharja Pillars. which is then implemented for the needs of journal publications on STMIK Raharja through web cices.ilearning.me. Keywords: Rinfo, Rinfo Sheet, Rinfo Form